2021
DOI: 10.1038/s41598-021-93315-4
|View full text |Cite
|
Sign up to set email alerts
|

A new inflammatory parameter can predict delayed intracranial hemorrhage following ventriculoperitoneal shunt

Abstract: Delayed intracerebral hemorrhage (DICH) secondary to ventriculoperitoneal (VP) shunt is considered to be a potentially severe event. This study aimed to investigate the association between a ratio of postoperative neutrophil-to-lymphocyte ratio to preoperative neutrophil-to-lymphocyte ratio (NLRR) and DICH secondary to VP shunt. We performed a retrospective review of patients who underwent VP shunt between January 2016 and June 2020. Multivariable logistic regression analysis was used to assess the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The most widely accepted hypothesis suggests a progressive vascular erosion and inflammatory vasculitis reaction resulting from the close contact between the catheter and the brain vessels, potentially in the context of a degenerative brain parenchymal disease [ 10 , 14 , 25 , 27 ]. A recent study identified an inflammatory parameter, the neutrophil-to-lymphocyte ratio, as a successful predictor of DICH following VPS, with an incidence of 40.6% in the identified subgroup, indicating the potential involvement of inflammatory pathways [ 33 ]. In a relevant series of 20 patients, Guo et al identified statistically significant independent risk factors for DICH, including age, history of craniotomy, and radiological features on initial CT scans [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely accepted hypothesis suggests a progressive vascular erosion and inflammatory vasculitis reaction resulting from the close contact between the catheter and the brain vessels, potentially in the context of a degenerative brain parenchymal disease [ 10 , 14 , 25 , 27 ]. A recent study identified an inflammatory parameter, the neutrophil-to-lymphocyte ratio, as a successful predictor of DICH following VPS, with an incidence of 40.6% in the identified subgroup, indicating the potential involvement of inflammatory pathways [ 33 ]. In a relevant series of 20 patients, Guo et al identified statistically significant independent risk factors for DICH, including age, history of craniotomy, and radiological features on initial CT scans [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the incidence of DICH was 16.4%, which corresponded to the incidence range of previous studies. The wide range of incidence may be related to the neglect of minor hematoma volume, lower frequency of postoperative CT scan examinations, and different inclusion and exclusion criteria in different studies[ 6 , 19 ]. We suppose that the real incidence range of DICH will be more accurate with careful surveillance, such as imaging and unified standards, in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed intracranial hemorrhage (DICH) refers to a subsequent cerebral hemorrhage that was not found in the first postoperative computed tomography (CT) scan of the VP shunt. Compared with other complications, DICH was regarded as a rare complication of VP shunts[ 5 , 6 ]. In 1985, Matsumura et al [ 7 ] provided a case report that was the first to describe DICH[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely accepted hypothesis suggests a progressive vascular erosion and inflammatory vasculitis reaction resulting from the close contact between the catheter and the brain vessels, potentially in the context of a degenerative brain parenchymal disease [10,14,25,27]. A recent study identified an inflammatory parameter, the neutrophilto-lymphocyte ratio, as a successful predictor of DICH following VPS, with an incidence of 40.6% in the identified subgroup, indicating the potential involvement of inflammatory pathways [33]. In a relevant series of 20 patients, Guo et al identified statistically significant independent risk factors for DICH, including age, history of craniotomy, and radiological features on initial CT scans [9].…”
Section: Dichmentioning
confidence: 99%